2011
DOI: 10.5455/spatula.20110514043359
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial, antioxidant activity and toxicity of extracts from the roots of <i>Rauvolfia vomitoria</i> and <i>R. caffra</i>

Abstract: AIM: This study aimed to investigate the antimycobacterial activity of total alkaloid and ethanolic aqueous extracts of Rauvolfia vomitoria and R. caffra. It further aimed to evaluate antioxidant activity and cytotoxicity effect of the extracts which would have shown high antimycobacterial efficacy. METHODS: The alkaloids from the roots of two plant species were extracted according to standard procedures. Antimycobacterial activity of the extracts was evaluated using a two fold microdilution method. The antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Therefore, we decided to isolate compounds from the stem bark, identify the major chemical constituents present and determine if they are responsible for the bioactivity of the plant. Our results confirm the reported antioxidant activity of the crude methanol extracts from Rauvolfia caffra [ 22 , 23 ]. However, isolated compounds from this plant have not yet been studied for their antioxidant activity.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, we decided to isolate compounds from the stem bark, identify the major chemical constituents present and determine if they are responsible for the bioactivity of the plant. Our results confirm the reported antioxidant activity of the crude methanol extracts from Rauvolfia caffra [ 22 , 23 ]. However, isolated compounds from this plant have not yet been studied for their antioxidant activity.…”
Section: Introductionsupporting
confidence: 92%
“…The main constituents isolated and identified from the stem bark of R. caffra are macrocaffrine, yohimbine, sarpagan, akuammicine, dihydroindole, indolenine, peraksine, oxindole, anhydronium, ajmaline, ajmalicine and geissoschizol. These alkaloids also have pharmacological activities, such as antimicrobial, anti-inflammatory, antimalarial, antioxidant, antitumor and antidiabetic properties [ 22 , 23 ]. Although herbal practitioners use Rauvolfia caffra in South Africa and some African countries for the treatment of a wide range of diseases, there are a limited number of studies into the chemistry of the underground and aerial parts of R. caffra as well as the bioactivity of the extracts.…”
Section: Introductionmentioning
confidence: 99%
“…The extracts from leaves of R. macrophylla and M. tomentosa exhibited better antibacterial activity than those obtained from their barks; this selective activity may be due the qualitative and/or quantitative difference in phytochemical contents of parts of the plants. The antibacterial activity obtained with R. macrophylla extracts may be due to the alkaloids present in this plant; in effect, Erasto et al [ 13 ] have demonstrated the anti-mycobacterial extracts properties of alkaloids extracts from R. macrophylla . Viscum album extracts from various parts of plant were active on all bacterial species used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…(1974/SRF-Cam)/BignoniaceaeEdema, cancer, gout, scrotal elephantiasis, pulmonary troubles, general body pain [30]Leavesβ-sitosterol, β-sitosterol-3- O -β- d -glucopyranoside, dehydroiso-α-lapachone, 2-acetylnaphtho[2,3-b]furan-4,9-dione, pomolic acid, 2-acetyl-6-methoxynaphtho[2,3-b]furan-4,9-dione, β-lapachone, tormentic acid, oleanolic acid, palustrine [31, 32]Antiprotozoal, antihelmintic, antibacterial, antifungal, antiviral, analgesic, anti-inflammatory antioxidant, anti-tumor [3133] Viscum album L. (2974/HNC)/LoranthaceaeAtherosclerosis, hypertension, cancer, headache, dizziness, palpitation [34, 35]LeavesConiferin, syringin, eleutheroside E, syringaresinol- O -glucoside, ligalbumosides A–E, alangilignoside C, kalopanaxin D, β-amyrin acetate, β-amyrin, lupeol, lupeol acetate oleanolic acid, betulinic acid, stigmasterol, β-sitosterol, trans -α-bergamotene, trans -β-farnesene, loliolide, vomifoliol, 5,7-dimethoxy-flavanone-4′- O -glucoside, 2′-hydroxy-4′,6′-dimethoxychalcone-4- O -glucoside, 5,7-dimethoxyflavanone-4′- O -[2′′- O -(5′′′- O - trans -cinnamoyl)-apiosyl]-glucoside), 2′-hydroxy-4′,6′-dimethoxychalcone-4- O -[2′′- O -(5′′′- O - trans -cinnamoyl)-apiosyl]-glucoside, 2′-hydroxy-3,4′,6′-trimethoxychalcone-4- O -glucoside, 2′-hydroxy-4′,6′-dimethoxychalcone-4- O -[apiosyl(1 → 2)]-glucoside, 5,7-dimethoxyflavanone-4′- O -[apiosyl-(1 → 2)]-glucoside, (2 S )-3′,5,7-trimethoxyflavanone-4′- O -glucoside, 4′- O -[β-apiosyl(1 → 2)]-β-glucosyl]-5-hydroxy-7- O -sinapylflavanone, 3-(4-acetoxy-3,5-dimethoxy)-phenyl-2 E -propenyl-β-glucoside, 3-(4-hydroxy-3,5-dimethoxy)-phenyl-2 E -propenyl-β-glucoside, 4′,5-dimethoxy-7-hydroxy flavanone, 5,7-dimethoxy-4′-hydroxy flavanone [36]Antihypertensive, cytotoxicity, vascular effects, antioxidant, antibacterial [34, 35, 37, 38] Rauwolfia macrophylla Ruiz & Pav. (1697/SRFK)/ApocynaceaeMeasles or itching rash, fever, swellings, rheumatism, hepatitis, pneumonia, abdominal pain, cough and toothache, headache, insomnia and palpitation of the heart, abscess, roundworm, tapeworm, hypertension, epilepsy, eye diseases, venereal diseases [39]Leaves, bark, rootsReserpine, rescinnamine, ajmaline, methyl reserpate, normacusine B, suaveoline, serpentine, perakine, vomilenine, peraksine, dihydroperaksine, norajmaline, ajmalicinine, ajmalicine, geissoschizol, pleiocarpamine, α-yohimbine, alloyohimbine, yohimbine [4043]Antimycobacterial and Antibacterial activity, antioxidant [13, 44, 45] …”
Section: Methodsmentioning
confidence: 99%
“…Other uses include convulsion, jaundice and gastrointestinal troubles [9]. The biological activities reported for this plant include anthelmintic, cytotoxic, anticancer [10,11], antimycobacterial, antioxidant activity [4,12], hepatoprotective [13], antispasmodial [14] and antipyretic [15,16] effects. About 50 alkaloids have been isolated from this plant, among which are reserpine, ajmaline, deserpidine, corynanthine, rescinnamine and yohimbine [3,17,18].…”
Section: Rauvolfia Vomitoriamentioning
confidence: 99%